Differences in the visual perception of the upper dental midline deviation between orthodontically completely treated and untreated patients - Laviana, Avi; Yakin Hasbullah, Irnamanda Dwipura; Sayuti, Elih; Mardiati, Endah; Noviaranny, Indah Yuri (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: A common reason for people to obtain orthodontic treatment is a misalignment between the upper dental midline and the midline of the face. The process of orthodontic treatment is considered to affect a patient's visual perception before and after the treatment, as well as their satisfaction with treatment, possibly due to the information received during treatment.  This study aimed to analyze this visual perception of dental midline deviation differences between orthodontically completely treated and untreated patients. Methods: This was a cross-sectional survey of 90 orthodontic patients, 49 completely treated patients who had completed orthodontic treatment and 41 untreated patients who had not started treatment. Patients were asked to complete a Google Form questionnaire for evaluating 12 intraoral smiling photos with midline deviation and a Likert scale. Bivariate statistical analysis with the Mann Whitney test was carried out to see differences in visual perceptions between two groups. Results: Completely treated patients perceive a 0-1 mm (LCN/L photos) midline deviation of the upper teeth as attractive, while untreated patients perceive a 0-2 mm (LCN photos) and 0-3 mm (L photos) deviation as attractive. The statistical analysis revealed a significant difference in patient perception between completely treated and untreated groups, with a p-value of 0.001 (p<0.05) and a mean score of 36.5 and 53.0, respectively. Conclusion: There are differences in visual perception between orthodontically completely treated and untreated patients. The group of completely treated patients is more sensitive to detecting a midline deviation of the upper teeth..Keywords : Upper dental midline deviation, visual perception, completely treated orthodontic patients, untreated orthodontic patients